Pengaruh Harga E-Service Quality, Terhadap Perilaku Impulse Buying : Studi Kasus Marketplace Shopee - Anita Karlina; R. Taufiq Nur Muftiyanto; Agus Suyatno (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
In the increasingly developing digital era, online buying and selling transactions have become the main choice for many consumers in Indonesia). Ease of access, a variety of product choices, and flexibility in payment and delivery are the main factors that make e-commerce platforms an attractive option for consumers. Shopee, one of the most popular e-commerce platforms in Indonesia, has succeeded in attracting consumer attention through good user experience, easy cash on delivery services, and adaptation to consumer lifestyles. Even though Shopee is relatively new compared to other platforms, this application is still the main choice for Indonesian consumers to shop online. In 2023, Sea Group, Shopee's parent company, recorded its first net profit of US$162.7 million since its IPO in 2017. Forrest Li, CEO of Sea Group, stated that this achievement was driven by market leadership in the e-commerce business, development of the digital financial services business, and stabilization of the performance of the digital entertainment business.